Investigating the effect of micro-riblets on the flow and micro-mixing behavior in micro-channel - Fiona Ling, Wang Ming; Khleif, Ali A.; Abdulbari, Hayder A. (Taylor & Francis, 2020)
Chaotic advection method is usually implemented to design any micro-mixing device, specifically micro-mixers, where the base or the top wide surface is structured for maximum mixing performance. This method comes with several drawbacks, such as the high-pressure drop caused by the structured inner surface. In the present work, V-shaped micro-riblets with the riblets size ranged between 20 and 100 µm are designed and structured on the side-walls of a rectangular T-shaped micro-mixers to test its mixing and flow enhancement performances at different flow rates for single and multiple phases flow. The micro-mixers were fabricated using a direct writing method with polydimethylsiloxane as a substrate. The flow and mixing behaviors of single and multiphase flow systems were investigated through monitoring the flow of the fluids flowing through the system using micro-Particle Image Velocimetry (µ-PIV). The results showed a flow enhancement up to ∼29% for a 60 µm of base-to-height riblet at an operating pressure of ∼200 mbar for a single-phase flow system. Larger micro-riblets were found to produce a thicker laminar sub-layer within the devices that narrowed the active core of the solution. When a two-phase flow system is introduced, the flow enhancement was observed in the water phase at operating pressure > 600 mbar and riblets dimension > 60 µm. On the other hand, the maximum mixing intensity of 52% was observed in 60 µm micro-riblets size indicating that the presence of micro-structure in the micro-mixer can enhance both the flow and mixing efficiency.